Efeitos centrais e periféricos da implantação de células tronco hematopoéticas associado ao uso de fator estimulador de colônia de granulócitos na insuficiência cardíaca experimental - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
Background: Immunologic and skeletal muscle morphology changes are associated with functional capacity impairment after myocardial infarction (MI), added central modifications. A better understanding of the hemodynamic and peripheral mechanism involved in heart failure is necessary to develop specific therapeutic strategies, as stem cells (SC) or granulocyte colony-stimulating factor (G-CSF) to slow or prevent muscular atrophy present in this syndrome beyond the deleterious immunologic changes. Aims: Therefore, the purpose of this study was to evaluate the effects of stem cells (SC) or/and granulocyte colony-stimulating factor (G-CSF) administration into heart and peripheral tissues after experimental myocardial infarction induction. Methods: In Balb/C was induced ligation of the left coronary artery. Animals in the control group underwent the surgical procedure without ligation of the artery. One week after the procedure, animals were treated with PBS (IM+PBS), G-CSF (IM+G-CSF) or G-CSF associated with hematopoietic CT (IM+G-CSF+CT). The animals were observed for a period of four weeks and underwent echocardiography, stress testing and collection of tissues (heart, lung, diaphragm, liver and peripheral muscle) for analysis of cytokines and structural changes. Results: The results demonstrate that all the treatments were able to reduce infarct, more evident following administration of G-CSF. Moreover, G-CSF induced response in the worst stress test (smaller total distance and final velocity achieved). Analysis of cytokines skeletal tissue demonstrated increased frequency of high producers of pro-inflammatory cytokines such as TNF-α, IL-6, IL-12, IFN-γ, IL-1-β and IL-4 in mice infarcted, resulting in imbalance in balance anti/pro-inflammatory immune response. The treatments had impaired negative when using G-CSF alone and satisfactory results when combined with the use of SCs. Conclusion: We conclude that using G-CSF alone appears to be responsible for amplifying the inflammatory process in infarcted animals leading to reduced functional capacity of skeletal muscle, which reflects in lower performance in exercise stress testing. In contrast, the use of G-CSF in association with hematopoietic CT appears to have a beneficial effect in modulating the inflammatory response and result in lower deleterious effect on the heart failure syndrome.
Keywords: Insuficiência cardíaca; Terapia celular; Colônia de granulócitos; Tecidos periféricos.; CIÊNCIAS BIOLÓGICAS